Prioritising non-native fish species for management actions in three Polish rivers using the newly developed tool-dispersal-origin-status-impact scheme - Błońska, Dagmara; Grabowska, Joanna; Tarkan, Ali S; Soto, Ismael; Haubrock, Phillip J (PeerJ, 2024)
BACKGROUND: Biological invasions are a major threat to global biodiversity, with freshwater ecosystems being among the most susceptible to the successful establishment of non-native species and their respective potential impacts. In Poland, the introduction and spreading of non-native fish has led to biodiversity loss and ecosystem homogenisation. METHODS: Our study applies the Dispersal-Origin-Status-Impact (DOSI) assessment scheme, which is a population-level specific assessment that integrates multiple factors, including dispersal mechanisms, origin, status, and impacts, providing a nuanced framework for assessing invasion risks at local and regional levels. We used this tool to evaluate the risks associated with non-native fish species across three major Polish rivers (Pilica, Bzura, and Skrwa Prawa) and to prioritise them for management actions. RESULTS: Using DOSI, we assessed eight non-native species identified in the three studied rivers: seven in both Pilica and Bzura and four in Skrwa Prawa. The DOSI assessment scheme identified high variability in the ecological impacts and management priorities among the identified non-native species. Notably, species such as the Ponto-Caspian gobies exhibited higher risk levels due to their rapid spread and considerable ecological effects, contrasting with other species that demonstrated lower impact levels and, hence, received a lower priority for intervention. CONCLUSION: The adoption of the DOSI scheme in three major rivers in Poland has provided valuable insights into the complexities of managing biological invasions, suggesting that localised, detailed assessments are crucial for effective conservation strategies and highlighting the importance of managing non-native populations locally.
Keywords: Biodiversity; Ecosystem; Poland; řeky; biodiverzita; Rivers; Species management; ryby; Biological invasions; Fishes; Invasive species; zavlečené druhy; Conservation of Natural Resources; Animals; zachování přírodních zdrojů; zvířata; Introduced Species; Risk assessment; ekosystém; Polsko